Not the Duke's Darling - Hoyt, Elizabeth, 1970-; Burrowes, Grace (New York : Forever, 2018)
Freya de Moray is many things: a member of the secret order of Wise Women, the daughter of disgraced nobility, and a chaperone living under an assumed name. What she is not is forgiving. So when the Duke of Harlowe, the man who destroyed her brother and led to the downfall of her family, appears at the country house party shes attending, she does what any Wise Woman would do: she starts planning her revenge. Christopher Renshaw, the Duke of Harlowe, is being blackmailed. Intent on keeping his secrets safe, he agrees to attend a house party where he will put an end to this coercion once and for all. Until he recognizes Freya, masquerading among the party revelers, and realizes his troubles have just begun. Freya knows all about his sins-- sins hed much rather forget. But shes also fiery, bold, and sensuous--a temptation he cant resist. When it becomes clear Freya is in grave danger, hell risk everything to keep her safe. But first, he will have to earn Freyas trust...by whatever means necessary.
Keywords: Nobility -- Fiction; Parties -- Fiction; Extortion -- Fiction; Revenge -- Fiction; Man-woman relationships -- Fiction; Romance fiction